Low temperature specifie heat of Th-U. - Luengo, C. A.; Catignola, J. M.; Sereni, J. G. R.; Sweedler, A.R.; Maple, M.B.; Huber, J.G.; Sereni, Julián (1971)
Fil: Luengo, C. A. Comisión Nacional de Energía Atómica; Argentina